Inclusion of electronic sports in the Olympic Games for the right (or wrong) reasons. Issue 3 (2nd July 2020) - Pack, Simon M.; Hedlund, David P.
ABSTRACT: With so many popular and unique sports played around the world, one of the most important challenges for the International Olympic Committee is deciding which ones merit inclusion in the Olympic Games. In recent years, a spirited debate has ensued surrounding electronic sports, also known as esports, and the possible inclusion of this type of competitive video gaming at the Olympic Games. Considerations centre around the sporting legitimacy of electronic sport, which games might be appropriate to play at events such as the Olympics, and whether esports epitomise the values and ideals promoted by the Olympic Movement. There may be substantial and contrasting information on the topic and these aforementioned questions, but the growing popularity and significance of esports are noteworthy. Over the years, numerous policy entrepreneurs and stakeholders, including governing bodies, intellectual property rights holders, teams, players and sponsors, have all put forward various agenda and policy solutions in response to these questions. In this article, multiple perspectives on the potential inclusion of esports at the Olympic Games are presented and discussed in the context of both the Multiple Streams Framework and Actor-Network Theory. It is the hope of the authors that this article will fuel further discussions on the important topic of the possible, future inclusion of esports at the Olympic Games.